Analisis Pelaksanaan Perkawinan Adat Suku Baduy dan Pelanggaran Adat yang Berimplikasi pada Pembatalan Perkawinan di Desa Kanekes, Banten - Akmal Maulana; Ahmad Zazili; M. Wendy Trijaya (Lembaga Yasin AlSys, 2025)
The Indigenous Baduy community is known for consistently maintaining its traditions, including in marriage practices, despite increasing modernization and interaction with the outside world that increasingly influence their way of life. This situation raises questions regarding how customary marriages are conducted and what types of violations may lead to the annulment of a marriage under Baduy customary law. This study aims to analyze the implementation of Baduy customary marriage and to identify customary violations that result in the invalidation of a marriage. An empirical legal research method with a normative–empirical approach was employed; primary data were obtained through direct observation and in-depth interviews with customary leaders (Puun, Jaro, and sesepuh adat) and members of the Baduy community in Desa Kanekes, Banten, while secondary data were collected from relevant literature, journals, and statutory regulations. The data were analyzed qualitatively by integrating empirical findings from the field with the prevailing norms of Baduy adat law and comparing them with national legal provisions. The results show that Baduy customary marriage is carried out through sacred processes such as bobogohan, ngariksa, and ngabokor, led by the Puun and Jaro in accordance with customary rules, and a marriage is deemed valid when it meets age requirements, obtains family approval, and receives the consent of customary authorities. Conversely, violations such as marrying an outsider, entering into marriage without the Puun’s approval, or failing to comply with prescribed ritual procedures result in the marriage being declared void and subject to customary sanctions. These findings affirm that Baduy customary law plays a crucial role in preserving cultural values and local wisdom, while also serving as concrete evidence of the reality of legal pluralism in Indonesia.